Influence of Water Hardness on Chronic Toxicity of Potassium Chloride to a Unionid Mussel (Lampsilis siliquoidea). (4th April 2023) - Wang, Ning; Dorman, Rebecca A.; Kunz, James L.; Cleveland, Danielle; Steevens, Jeffery A.; Dunn, Suzanne; Martinez, A. David
Abstract: Elevated concentrations of potassium (K) often occur in effluents from wastewater treatment plants, oil and gas production operations, mineral extraction processes, and other anthropogenic sources. Previous studies have demonstrated that freshwater mussels are highly sensitive to K in acute and chronic exposures, and that acute toxicity of K decreases with increasing water hardness. However, little is known about the influence of hardness on the chronic toxicity of K. The objective of our study was to evaluate the chronic toxicity of K (tested as KCl) to a commonly tested unionid mussel (fatmucket, Lampsilis siliquoidea ) at five hardness levels (25, 50, 100, 200, and 300 mg/L as CaCO3 ) representing most surface waters in the United States. Chronic 28‐day K toxicity tests were conducted with 3‐week‐old juvenile fatmucket in the five hardness waters using an ASTM International standard method. The maximum acceptable toxicant concentrations (geometric mean of the no‐observed‐effect concentration and the lowest‐observed‐effect concentration) increased from 15.1 to 69.3 mg K/L for survival and from 15.1 to 35.8 mg K/L for growth (length and dry wt) and biomass when water hardness was increased from 25 mg/L (soft) to 300 mg/L (very hard). These results provide evidence to support water hardness influence on chronic K toxicity to juvenile fatmucket. However, the chronic effect concentrations based on the more sensitive endpoint (growth or biomass) increased only 2.4‐fold from the soft water to the very hard water, indicating that water hardness had a limited influence on the chronic toxicity of K to the mussels. These results can be used to establish chronic toxicity thresholds for K across a broad range of water hardness and to derive environmental guideline values for K to protect freshwater mussels and other organisms. Environ Toxicol Chem 2023;42:1085–1093. Published 2023. This article is a U.S. Government work and is in the public domain in the USA.